A citation analysis of the Philippine Sociological Review, 1953-2007 - Vinagrera, Emmanuel R. (School of Library and Information Studies, University of the Philippines Diliman, 2009)
Citation analysis provides an objective supplementary tool for the development of collection management policies. Journals are subject-specific and are indicative of the discourse in the subject field.